Impact of Domestic and Foreign Capital on Economic Growth and Employment: Empirical Analysis of 43 Lower Middle-income Economies - Oli, Sudan Kumar (Economic Journal of Development Issues, 2024)
The purpose of this paper is to investigate the impact of domestic and foreign capital inflows on economic growth and employment in lower-middle-income countries (LMICs). To analyze the impact of domestic and foreign capital on economic growth and employment, this study used panel data from 43 LMICs spanning the period 1990 to 2021. The study employed the Panel Ordinary Least Squares (POLS) estimation method for the baseline regression analysis. However, the Breusch-Pagan test suggested that the estimation model is not suitable for GDP per capita growth (GDPPCG) under POLS estimation. Thus, the Generalized Least Squares (GLS) procedure has been employed to examine the impact of domestic and foreign capital on economic growth. After the Hausman specification test, we used a random-effect estimation procedure for the conclusion of the impact analysis under panel data analysis techniques. This study concludes that there is a positive impact of both domestic and foreign capital on economic growth in LMICs. However, only foreign capital inflow has a significantly positive impact on employment. The impact of domestic and foreign capital inflows on economic growth and employment differs significantly. Therefore, this study advises that, for LMICs, domestic capital is more important for growth and employment.